Examining the effect of gender, education and religion on attitudes toward gender equality in Nigeria - Daniel Tuki (Politics, Groups, and Identities, 2025)
Using novel survey data collected from the states of Kaduna and Edo in Nigeria's Northern and Southern Regions respectively, this study examined the correlates of gender egalitarian attitudes with a particular focus on gender, educational attainment, religious affiliation, and the region where the respondents resided. The regression results showed that educational attainment and being female positively correlated with support for gender equality in the two states. Muslim affiliation negatively correlated with support for gender equality in Kaduna; however, in the case of Edo, it was statistically insignificant. Moreover, residing in Northern Nigeria negatively correlated with support for gender equality. When I broke down the data based on gender (males and females) and religious affiliation (Muslims and Christians) and compared the subgroups across the two states, the descriptive results showed that Muslims in Edo were more supportive of gender equality than both Christians and Muslims in Kaduna. Males in Edo were also more supportive of gender equality than both females and males in Kaduna. This suggests that it would be misleading to lump respondents from both states into the same category based on gender or religious affiliation because they differ considerably.
Keywords: J16; I25; Z12; 330; Gender equality; attitudes; education; religion; Kaduna; Edo; Nigeria